Validity and Reliability of Resilience Scale for Islamic Boarding School Students - Destiana Rizki Hayatini; Dimyati Dimyati (Bina Nusantara University, 2020)
The research aimed to examine the content validity and resilience scale reliability that was developed based on the theory of Reivich and Shatte. The measuring instrument consisted of 32 items which resulted from a modification of the instruments made by Reivich and Shatte. The instrument had seven aspects of resilience, namely emotion regulation, impulse control, optimism, causal analysis, empathy, self-efficacy, and reaching out. The research sample amounted to 150 respondents consisting of Islamic Boarding School students in Purworejo, Central Java, boys and girls aged 11-18 years. The items in the measuring instruments were analyzed using the Gregory formula with the help of Ms. Excel program; then, the Cronbach Alpha formula was analyzed using the SPSS program. Based on the analysis of content validity with two experts’ judgments and the validity index of 1, it means that the instrument’s validity is very high. As for the reliability test results, the value of Cronbach’s Alpha item resilience scale is 0,753. This shows that the resilience scale item has good reliability. Based on these data, resilience instruments can be said to be valid and reliable to measure the resilience of Islamic Boarding School students.